Cosmology and Heroic Values in the Takna' Lawe' Epic of the Kayan Community of West Kalimantan: (Kosmologi dan Nilai Kepahlawanan dalam Sastera Epik Takna' Lawe' Komuniti Kayan Kalimantan Barat) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
The cosmological history of the Malays has always been a contentious issue. Its concepts, ideas and challenges have frequently been debated. Discussions frequently concern the role of Islam as the basis of the inclusive nature of Malay cosmology. In line with this, this article discusses the framework, interaction and consolidation of Islam in Malay cosmology based on historical evidence. Also discusses are the opposing views of orientalists that have studied Malay cosmology from a colonialist point of view. The emergence of thought other than Islam, such as secular and socialist ideology, has had a further effect on the Malay-Islamic weltanschauung, and on Malay society as a whole. The social system within Malay cosmology has been eroded and has resulted in a society whole principles and thought differs from that of the Malay society of old which placed great importance on the Islamic value of brotherhood.Keywords: cosmology, Malay, Islam, tradition, westernization